Additive Manufacturing Technologies: 3D Printing, Rapid Prototyping, And Direct Digital Manufacturing [2nd ed.] - Gibson, Ian; Rosen, David; Strucker, Brent (London; Springer, 2015)
This book covers in detail the various aspects of joining materials to form parts. A conceptual overview of rapid prototyping and layered manufacturing is given, beginning with the fundamentals so that readers can get up to speed quickly. Unusual and emerging applications such as micro-scale manufacturing, medical applications, aerospace, and rapid manufacturing are also discussed. This book provides a comprehensive overview of rapid prototyping technologies as well as support technologies such as software systems, vacuum casting, investment casting, plating, infiltration and other systems.
Keywords: Manufacturing